Kajian Yuridis Tentang Kelalaian Petugas Bank Terhadap Surat Peringatan Lelang Tanpa Tanda Tangan Nasabah (Studi Kasus Perkara No. 40/Pdt.G/2020/PN.Mdn) - Ferawati Br.Tarigan; Sunarmi Sunarmi; Sutiarnoto Sutiarnoto; Mahmul Siregar (Jurnal Pencerah Bangsa, 2023)
Law Number 8 of 1999 concerning Consumer Protection which is explained in Article 18 concerning Standard Clauses, it explains the provisions in making an agreement that includes standard clauses. Customers as consumers are required to receive legal protection for the use of service products offered by the bank. Guarantees with Mortgage are given through the Deed of Granting Mortgage (APHT), if the debtor as the provider of Mortgage is in default (default). Execution of the Mortgage Guarantee is the last step taken by the creditor as the recipient of the Mortgage if the creditor or bank in collecting non-performing financing is not effective enough, then based on Article 20 paragraph (1) letter b of Law Number 4 of 1996 concerning Mortgage, it can be conducted by way of public auction.This study uses a normative juridical approach. The normative juridical approach is an approach that is based on the main legal material by examining theories, concepts, legal principles and laws and regulations related to this research.